Overweight and Obesity above 18 years of Age in An Urban Population - Kamboj, Amit Kumar; Chopra, Harivansh; Singh, Jai Veer; Garg, Sunil Kumar; Bajpai, Shailendra Kumar (Indian Journal of Community Health, 2017)
Background: Today however, as standard of living continues to rise, weight gain and obesity are posing a growing threat to health in both developed and developing countries and affecting children as well as adults. Indeed, it is now so common that it is replacing the more traditional public health concern including under nutrition and infectious diseases. Overweight and obesity is a major risk factor for high morbidity and mortality. Obesity is an independent risk factor for chronic heart disease related morbidity and mortality. Aims and Objectives: To find out the prevalence of overweight & obesity and to suggest measures for prevention of overweight and obesity in adult population. Material and Method: To cover a sample size of 1152 in Urban Health Centre area population ?18 years every fifth family was selected by systematic random sampling from the total of 1698 families registered at Urban Health Centre. They were interviewed personally and information was collected about sociodemographic characteristics, personal factors, and measurements of weight, height, waist and hip circumference of the individuals were taken to calculate Body Mass Index (BMI) and Waist Hip Ratio (WHR). Results: Prevalence of overweight (BMI -25-29.99) and obesity (BMI ?30) being 28.0% and 8.0% respectively. Prevalence of abdominal obesity was 25.8%. About two-third (66.9%) of abdominal obesity rightly corresponded with the high BMI (25+). Conclusion: The prevalence of overweight and obesity is increasing in urban area of Meerut, more in females than males and it is being affected by various socio-demographic correlates.